The Soul of Film Theory - Cooper, S. author. aut Link
X, 209 p.
Keywords: In this innovative book, Sarah Cooper revisits the history of film theory in order to bring to the fore the neglected concept of the soul and to trace its changing fortunes. The Soul of Film Theory charts the legacy of this multi-faceted, contested term, from the classical to the contemporary era.